Can home-based training influence mood states and quality of life in Paralympic boccia athletes? - Sidcley Felix Arruda; José Igor Vasconcelos de Oliveira; Ciro Winckler; André Santos Costa; Pedro Pinheiro Paes Neto; Mário Antônio Moura Simim; Saulo Fernandes Melo Oliveira (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
To verify the influence of home-based exercise and the type of physical limitation on the mood and quality of life were analyzed 34 Brazilian paralympic boccia athletes (with functional classes BC1 = 8, BC2 = 8, BC3 = 9, and BC4 = 9) of both genders, with different disabilities (e.g., cerebral palsy, quadriplegia, polio, congenital malformation, and muscular dystrophy). Profile of the Mood States and Quality of Life questionnaires were sent via apps through social media in electronic forms, and distributed throughout the country, in the shape of a snowball. To compare the typical characteristics of exercise at home in social isolation in the domains of mood state and quality of life, the independent t-test and Mann-Whitney were used. Then, to verify the influence of home training characteristics in isolation in specific groups of athletes (with and without cerebral palsy/with and without assistance) on the domains of mood state and quality of life, an analysis of covariance. No relevant differences exist between mood states and quality of life among the different demographic information analyzed. However, when controlling for comparisons through training covariates and the frequency used, it was found that the perception of quality of life under the "physical" domain presents significant differences among the analysis groups. The frequency of training in question may be enhanced by support covariates and the type of disability, significantly influencing their perceptions of quality of life.